TERRITORIAL PECULIARITIES OF DIFFIRENTIAL ASSESSMENT OF PHYSICAL FITNESS OF RURAL SCHOOLCHILDREN (American Journal of Interdisciplinary Research and Development, 2022)
In addition, the kundalik life support of a person meets the requirements of various groups for building muscle mass.